2020
DOI: 10.5935/1518-0557.20200054
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: New adaptation for IVF laboratory protocols

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) widely known as COVID-19 was first reported in late December 2019, in China. Since then this novel coronavirus has spread throughout the world. Our return to normal life will not take long, for we are in a phase where the COVID-19 curve is stabilizing. ART services must return to operation, since infertility is also a disease and treatment has to start. Before resuming ART treatments, it is very important to consider local and national regulations. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 12 publications
0
27
0
1
Order By: Relevance
“…Exceptions were patients currently "in-cycle" or requiring urgent fertility preservation due to cancer treatment [3]. More recently, in Europe, with successful mitigation strategies against the pandemic, societies have allowed gradual resumption of ART procedures [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Exceptions were patients currently "in-cycle" or requiring urgent fertility preservation due to cancer treatment [3]. More recently, in Europe, with successful mitigation strategies against the pandemic, societies have allowed gradual resumption of ART procedures [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that more than 60% of COVID‐19 patients were identified to be asymptomatic and may spread virus (Qiu, 2020). Therefore, as Andrabi SW et al (Andrabi et al, 2020) reported, some stricter processes need to be implemented and our suggestions can be used as a supplement. Although the levels of messenger RNA might not be absolutely equal to protein, our finding supports the hypothesis that the chance of SARS‐CoV‐2 passing through germ cells to offspring is very low.…”
Section: Discussionmentioning
confidence: 99%
“…In COVID-19 positive patients, home collection and proper care can be an ideal way. Andrabi et al [17].…”
Section: Recommendation Based On Expert Opinionmentioning
confidence: 99%